Experimental and computational fluid dynamics (CFD) studies of gas-liquid flow in bends - Abdulkadir, Mukhtar. (2011)
Within the oil industry there is a need to measure and predict the form of the multiphase liquid and gas flows that are present within oil production and processing pipelines. Knowledge of the flow regimes present allows the engineer to optimise the configuration of the pipeline and downstream processes to achieve the most, economic and reliable design. The applications of these technologies are collectively known as flow assurance. Within oil production systems, one component which has received little attention is the characterisation of the multiphase flow around bends under various process conditions. To predict the flow regimes in greater details requires the development of instrumentation that can measure and characterise the flow within the pipes.